2008
DOI: 10.1152/ajprenal.00088.2008
|View full text |Cite
|
Sign up to set email alerts
|

Vasopressin regulates the renin-angiotensin-aldosterone system via V1a receptors in macula densa cells

Abstract: A. Vasopressin regulates the renin-angiotensin-aldosterone system via V1a receptors in macula densa cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
64
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 68 publications
(72 citation statements)
references
References 40 publications
7
64
0
1
Order By: Relevance
“…Interestingly, these animals also have a reduction in activation of the reninangiotensin system, whereby release of renin from the kidney is reduced in the absence of V1a-receptor-mediated signalling. 5 This evidence links the increase in metabolic rate back with a reduction in angiotensin that we observed in our study. Moreover, other studies have shown that blockade of angiotensin with AT 1 receptor antagonists also reduces body fat, without increasing water intake.…”
supporting
confidence: 78%
“…Interestingly, these animals also have a reduction in activation of the reninangiotensin system, whereby release of renin from the kidney is reduced in the absence of V1a-receptor-mediated signalling. 5 This evidence links the increase in metabolic rate back with a reduction in angiotensin that we observed in our study. Moreover, other studies have shown that blockade of angiotensin with AT 1 receptor antagonists also reduces body fat, without increasing water intake.…”
supporting
confidence: 78%
“…Previously, we showed that the stimulation of V1aR in the macula densa is the first step of renin production and the deficient of V1aR in macula densa causes hyporeninemic hypoaldosteronism. 19,20 This study shows that the defect in urinary acid excretion in V1aR Ϫ/Ϫ mice is associated with functional defects in the vasopressin V1aR and subsequent changes in Rhcg, H-K-ATPase, and H-ATPase in the intercalated cells of the collecting ducts. Therefore, V1aR is essential not only for aldosterone production but also for tubular effects of aldosterone.…”
Section: V1armentioning
confidence: 73%
“…18 We have found that the deficient of V1aR causes hyporeninemic hypoaldosteronism. 19,20 Therefore, we investigated acid-base balance in mice lacking V1aR (V1aR Ϫ/Ϫ ). Furthermore, because the target site of aldosterone for acid-base regulation is the intercalated cells of the collecting duct, we established a new cell line of the intercalated cells.…”
mentioning
confidence: 99%
“…We have reported that V1a receptordeficient mice showed decreased renin-angiotensin-aldosterone (RAA) system and V2R-AQP2 system. 25 V1aR in the macula densa cells regulates both the RAA system and the V2R-AQP2 system. Increased V1aR in acidosis may stimulate the RAA system and the V2R-APQ2 system, resulting in the increase in AQP2 expression in the collecting ducts in this study.…”
Section: Discussionmentioning
confidence: 99%